Accommodative–vergence disorders in a paediatric ophthalmology clinical setting in Argentina - Iurescia, Alejandra (2023)
Purpose: To determine the frequency of potential non-strabismic accommodative-vergence anomalies (NSAVA) and investigate associations between NSAVA, refractive errors, and age among children attending a paediatric ophthalmology clinic. Methods: This study included children and adolescents aged 5-19 years attending an ophthalmology clinic with at least two follow-up visits. At their first visit, children had a comprehensive ophthalmic examination, including refractive error measurement by cycloplegic autorefraction, and spectacles were prescribed if necessary. At the second visit, children had an examination of best-corrected visual acuity, convergence, and accommodation to identify potential NSAVA. The relationship between age, sex, heterophoria refractive error, and potential NSAVA was assessed by a multivariable logistic regression model. Results: A total of 384 children and adolescents were evaluated. Their mean age was 10.97 ± 3.07 years and 58.9% were females. Forty-two percent of children failed the NSAVA tests and 34.1% had myopia (≤-0.50 D). Children who failed NSAVA tests self-reported a higher proportion of reading problems (73.7%) compared to those who passed the tests (26.3%; p < 0.001). Children with self-reported reading problems were more likely to have accommodative infacility (57.9%) compared with children without (42.1%; p < 0.001). Refractive error and age were not associated with failure in NSAVA tests (p > 0.05). Conclusions: NSAVA was a frequent cause of vision problems found in a sample of children from an ophthalmology paediatric clinic. Thus, further research is necessary to understand the potential of public health policies to prevent, refer, diagnose, and treat those conditions.